2013
DOI: 10.3389/fendo.2013.00045
|View full text |Cite
|
Sign up to set email alerts
|

FA1 Induces Pro-Inflammatory and Anti-Adipogenic Pathways/Markers in Human Myotubes Established from Lean, Obese, and Type 2 Diabetic Subjects but Not Insulin Resistance

Abstract: Aims: Delta like 1/fetal antigen 1 (Dlk1/FA1) is a protein secreted by hormone producing cells in adult human and mice that is known to inhibit adipogenesis. Recent studies demonstrated the role of Dlk1/FA1 in inducing insulin resistance in mice. To investigate the involvement of circulating Dlk1/FA1 in insulin resistance and type 2 diabetes in human subjects, we studied the effects of chronic FA1 on the intermediary metabolism in myotubes established from lean, obese, and type 2 diabetic (T2D) subjects.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…The picture regarding IL6 is more mixed. While we found IL6 secretion to be higher in T2D hSMC, as did Bouzakri et al after TNFa treatment of ND myotubes [ 11 ], others found no difference from ND [ 14 , 35 ] or even decreased release [ 34 ]. The observations that MCP-1 mRNA is elevated in T2D hSMC [ 12 , 36 ] and after TNFa treatment, and that secretion is also elevated in the later case [ 11 ], would be congruent with our results regarding MCP-1 release.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The picture regarding IL6 is more mixed. While we found IL6 secretion to be higher in T2D hSMC, as did Bouzakri et al after TNFa treatment of ND myotubes [ 11 ], others found no difference from ND [ 14 , 35 ] or even decreased release [ 34 ]. The observations that MCP-1 mRNA is elevated in T2D hSMC [ 12 , 36 ] and after TNFa treatment, and that secretion is also elevated in the later case [ 11 ], would be congruent with our results regarding MCP-1 release.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, the current report looks at only a small number of potential myokines. The decision was made to take a targeted approach, focusing on a limited number of factors, including several that have been under study by others [ 11 14 , 33 36 ], as well as factors for which there is evidence that they could possibly play roles in the diabetic phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing results from various metabolic assays conducted at three different days in myotubes established from the same donors in accordance with our protocols (73,92,144) shows that day-today variation is high, while within-day variation is small. Absolute rates of glucose uptake and glycogen synthesis can differ twofold between studies.…”
Section: Reproducibilitymentioning
confidence: 89%
“…In addition to studies on primary insulin resistance in diabetic myotubes, various aspects of insulin resistance induced by hyperinsulinaemia (48,52,68,165), hyperglycaemia (48,66,73,(165)(166)(167)(168), hyperlipidaemia (67,73,93,155) and other agents (92,144,169) have been investigated in human myotubes. Please refer to the relevant literature for further reading, as induced insulin resistance in skeletal muscle/myotubes is beyond the scope of the present review.…”
Section: Myotubes Established From T2d Subjects During Acute Insulin mentioning
confidence: 99%